Synchronization Response And Conception Rate With Ovsynch Protocol In Buffalo Under Field Condition - Girhepunje, B.S.; Pawshe, C.H.; Deshmukh, S.G.; Ingawale , M.V. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A total 30 cyclic buffaloes were selected from village Lakhani District Bhandara (MS) and divided into three equal groups. The selected buffaloes were treated with 2 ml normal saline i/m for 1st group, PGF2α (Cloprostinol 500 mcg) 11 days apart randomly and AI was done at observed oestrus for 2nd group and GPG - Ovsynch protocol (GnRH + PG + GnRH on day 0, 7 & 9, respectively) for 3rd group with fixed time AI 18-24 hrs later. The overall oestrus response was 20, 50 and 80 % in Group I, II and III, respectively. The average duration for onset of oestrus was 177.5 ± 24.50 hrs, 60.80 ± 2.86 hrs and 70.62 ± 14.82 hrs in Group I, II and III, respectively. The average length of oestrus was 16 ± 2.00 hrs, 14.2 ± 0.66 hrs and 14.87 ± 0.87 hrs in Group I, II and III, respectively. The corresponding average score for intensity of oestrus was 43 ± 1.00, 35.00 ± 2.16 and 39.37 ± 2.14 in three groups. The conception rate obtained was 10, 30 and 40 % in Group I, Group II and Group III, respectively. The ovsynch protocol was better for improving conception rate in field buffaloes.
Keywords: Buffalo; Oestrous synchronization; Conception rate; Ovsynch protocol